An integration of genome-wide survey, homologous comparison and gene expression analysis provides a basic framework for the ZRT, IRT-like protein (ZIP) in foxtail millet - Zheng, Jie; Ma, Yunxiao; Liang, Yu; Zhang, Tianhan; Chen, Chang; Amo, Aduragbemi; Wang, Wenyu; Ma, Fangfang; Han, Yuanhuai; Li, Hongying; Hou, Siyu; Yang, Yang (Frontiers in Plant Science, 2024)
Essential mineral elements such as zinc and iron play a crucial role in maintaining crop growth and development, as well as ensuring human health. Foxtail millet is an ancient food crop rich in mineral elements and constitutes an important dietary supplement for nutrient-deficient populations. The ZIP (ZRT, IRT-like protein) transporters are primarily responsible for the absorption, transportation and accumulation of Zn, Fe and other metal ions in plants. Here, 14 ZIP transporters in foxtail millet (SiZIP) were systematically characterized and the phylogenetic relationship with ZIPs in other species was clarified. SiZIPs display rich spatiotemporal expression characteristics in foxtail millet, suggesting their diverse functions. Furthermore, multiple SiZIPs demonstrated significant responses to Fe, Cd, Na, and K metal ions, as well as drought and cold stresses, indicating that they might be extensively involved in the transport of metal ions and osmotic regulation under abiotic stresses. Based on homologous comparisons, expression characteristics and previous studies, the functions of SiZIPs were predicted as being classified into several categories: absorption/efflux, transport/distribution and accumulation of metal ions. Simultaneously, a schematic diagram of SiZIP was drawn. This work provides a fundamental framework for the transport and accumulation of mineral elements and will facilitate the quality improvement of foxtail millet.